Factors Influencing Internet Financial Reporting in Infrastructure Firms - Dea Khusnul Khotimah; Dini Wahjoe Hapsari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Financial reporting on the internet has attracted the attentions of financial services authorities, thus making public companies obliged to implement internet financial reporting. However, there are still public companies that have not implemented internet financial reporting. In addition, some companies have implemented internet financial reporting but, do not disclose complete information per regulations. The purpose of this research is to investigate the impact of company size, listing age, and foreign listing status on the application of internet financial reporting. Quantitative research methods have been applied in this study. This study's population consists of infrastructure sector companies listed on the Indonesia Stock Exchange between 2016 and 2020. The researcher used a purposive sampling technique in selecting sample. The sample used in this study was 35 companies with five years of observation.  Information for this research comes from the company's annual report, website information, financial services authority regulations, and previous research. Panel data regression analysis technique has been used in this study and it was processed using EViews 10. The results show that the independent variables of company size and foreign listing status have no impact on internet financial reporting. However, variable listing age has a significant positive impact on internet financial reporting.